KEMAMPUAN KONSELING MAHASISWA CALON GURU SEBAGAI PROFESIONAL KONSELOR DI SD/MI - Taufiq , Moh.; Nurdianah, Lutfiyan; Zuhdan, Muchammad Tazdad (At- Ta'lim : Jurnal Pendidikan, 2024)
One of the duties of a teacher is to be a guide or what could also be called a counselor for their students. Teachers who act as counselors must be able to guide students in choosing educational programs at school according to their abilities, interests and aspirations. In addition, you must also be skilled in helping students to solve problems and make healthy adjustments. Therefore, students must have the provisions and abilities to act as counselors at school. This research aims to find out how much students' abilities are to prepare themselves as counselors at school and how to improve these abilities for students.This research uses descriptive qualitative research. The subjects in this research were PGSD/PGMI students in Surabaya who were/had taken guidance and counseling courses. Based on research data and results, prospective elementary/MI student teachers understand the theory, principles, techniques and procedures of guidance and counseling in elementary schools, however, there is a gap between theoretical understanding and its application, including how to prepare a service implementation plan (RPL) and how to identify characteristics. students directly. This is proven by the results of the questionnaire where of the 93.5% of respondents who stated that they understood the theories, principles, techniques and procedures of guidance and counseling, only 21.7% understood their implementation. To deepen your insight regarding counseling guidance services and improve students' counseling skills, do lots of practice, both in simulations and in the field, in order to increase your sensitivity as a counselor. By implementing these steps, it is hoped that prospective elementary/MI teacher students can improve their teaching skills so that they can provide more effective counseling services and support optimal student development in the Madrasah Ibtidaiyah/Primary School environment.